Potential TWA changes for gas monitoring instruments are alarming - P Aspinall (The Australasian Institute of Mining and Metallurgy, 2024)
Safe work Australia (SWA) has a number of proposed amendments to existing Workplace Exposure Standard (WES) values that may dramatically change how mining workplaces using personal gas monitoring instruments will operate. In consultation with leading gas monitor manufacturers and distributors, an assessment of common Australian alarm settings values and analysis of potential frequency of increased alarm likelihoods has been conducted. This assessment explores the relationships between current monitoring practices, using instruments as health and not just safety tools and identify what will be needed to minimise worker ‘alarm fatigue’ and for common tasks to continue safely. This paper provides the necessary information to aid industry and hygienists to be ‘future ready’ given the likely impact that order of magnitude reductions in time weighted average (TWA) values for NO2, SO2, H2S and other common gases will have on current working practices. Reductions to gas alarm values will provide significant challenges to existing work methods and will require, practical application of the pending future values. Improvements and awareness of instrument capabilities by safety and hygiene professionals will better utilise gas monitors real-time data monitoring capacity and no longer be just ‘safe or not-safe’ instruments. The presentation seeks to promote the practical steps required in setting alarms based on risk consequence and likelihood, increase general awareness of the tools and data available in modern instruments and will enable industry professionals to better manage the challenges of any potential future changes.